Volleyball Athlete's Anxiety: The Role Of Religiusity And Peer Support - Alfathra Mallaena; Hadi Pajarianto; Suaib Nur (JUARA : Jurnal Olahraga, 2022)
Anxiety is a form of human expression when facing stressful situations, including volleyball athletes. This study aims to (a) identify the relationship between religiosity and anxiety in volleyball athletes, (b) identify the relationship between peer support with volleyball athlete anxiety, and (c) know the relationship between religiosity and peer support together on the anxiety of volleyball athletes. This research is quantitative correlational research involving 110 respondents. Data analysis using SPSS Statistics 26. The results showed that religiosity and peer support stated that partially or simultaneously had a positive and significant effect on volleyball athletes' anxiety when competing. From this research, it can be concluded that volleyball achievement is strongly related to the level of religiosity and peer support of athletes. The contribution of this research is expected to be the attention of athletes and coaches that volleyball matches are not only related to physical training and skills but also must be supported by habituation of religious behaviour that can be applied in the form of prayer, worship, and other instruments to overcome athlete's anxiety.